2021
DOI: 10.1186/s41235-021-00343-9
|View full text |Cite
|
Sign up to set email alerts
|

White civilians’ implicit danger evaluation of police officers underlies explicit perception of police

Abstract: The role of implicit processes during police-civilian encounters is well studied from the perspective of the police. Decades of research on the “shooter bias” suggests that implicit Black-danger associations potentiate the perception of threat of Black individuals, leading to a racial bias in the decision to use lethal force. Left understudied are civilians’ possible associations of police with danger and how such associations pervade behavior and explicit views of the police. The current work begins to addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…the Chinese iconograph) is influenced by their implicit evaluation of the prime stimulus (e.g., police officer), effectively measuring one9s implicit attitude towards police officers. Previous work using the AMP has shown that people associate threat more with police than non-police (Olivett & March, 2021) and I expected similar results.…”
Section: Affect Misattribution Procedures (Amp)supporting
confidence: 67%
See 1 more Smart Citation
“…the Chinese iconograph) is influenced by their implicit evaluation of the prime stimulus (e.g., police officer), effectively measuring one9s implicit attitude towards police officers. Previous work using the AMP has shown that people associate threat more with police than non-police (Olivett & March, 2021) and I expected similar results.…”
Section: Affect Misattribution Procedures (Amp)supporting
confidence: 67%
“…These may include a lowered trust in police, more negative perceptions of law enforcement, and a change in behavioral intentions towards police such as an aversion to calling the police for help or a refusal to comply with police orders. Implicit attitudes towards police have been shown to be associated with explicit attitudes (i.e., how much people self-report liking or dislike the police, Olivett & March, 2021;Stults, 2023), yet the role of vicarious exposure to violence in establishing an explicit lack of trust in or negative beliefs towards police remains unstudied. As public perceptions and trust regarding police may play a pivotal role in establishing positive police-civilian relations, it is imperative to further investigate the relationship between exposure to police violence and trust in police.…”
Section: Psychological Consequences Of Police-threat Associationsmentioning
confidence: 99%
“…Yet, police-danger associations and defensive responses might also affect several other downstream attitudes and behaviors absent or prior to a police presence. Our previous work, for example, demonstrates that automatic police-threat attitudes predict more negative explicit attitudes of the police over and above automatic police-negative evaluations (Olivett & March, 2021). Meaning, police-threat associations are a negative influence on explicit attitudes of the police.…”
Section: Discussionmentioning
confidence: 98%
“…Although the explicit attitudes measured by Olivett and March (2021) captured general positive-to-negative views of the police, automatic police-danger evaluations may also relate to more specific attitudes about policing and police reform. Supporting this idea, self-reported emotional fear of the police predicts support for defunding the police, as well as intentions to engage in defensive legal socialization (i.e., having “the talk” about the police with one’s children; Pickett et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation